Strategy for the Formation of Student Manners Based on Islamic Character Education in the Dynamics of Globalization at MTS Muallimin UNIVA Medan - Aulia Khairani; Selamat Pohan (Journal of General Education and Humanities, 2026)
Globalization and rapid digital development have increasingly challenged students’ moral conduct (adab), particularly within Islamic educational institutions, as exposure to unfiltered digital content, social media influence, and external cultural values contributes to declining discipline and ethical behavior. This study examines how Islamic schools can effectively address these challenges through character-based adab education. The objective of this study is to analyze the strategies used in forming students’ adab based on Islamic character education in response to globalization dynamics at MTs Muallimin UNIVA Medan. This research employed a qualitative descriptive approach. Data were collected through in-depth interviews, participant observation, and documentation involving Islamic education teachers, homeroom teachers, counseling teachers, and students. Data analysis was conducted through data reduction, data display, and conclusion drawing to ensure the credibility of the findings. The results indicate that students’ adab formation is implemented systematically through teachers’ role modeling, religious habituation, the integration of adab values into classroom learning, religious and extracurricular programs, and persuasive, humanistic guidance. A religious school culture, teacher consistency, parental involvement, and structured institutional programs support these strategies. However, challenges remain, including the influence of social media, external peer environments, and limited parental supervision. Overall, Islamic character-based adab education at MTs Muallimin UNIVA Medan is effective in strengthening students’ moral resilience and ethical awareness, enabling them to respond wisely and responsibly to the challenges of globalization and the digital world.